ANALISIS PENDAPATAN USAHATANI TOMAT APEL DI DESA ALAKASING KECAMATAN PELING TENGAH KABUPATEN BANGGAI KEPULAUAN - Ismail Djamaluddin; Irsan Z Tatu; Noprianti Noprianti; Trianto Enteding (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Apple tomatoes the shape of the fruit is round, sturdy, and slightly hard like apples or pears this type of tomato is more suitable for planting on high plates. Tomato plants originate from the west coast of South America and grow wild around Ecuador, the northern part of Chile, and Galapagos Island, but domestication or cultivation was not first carried out in that place This study aims to find out how much income and feasibility level farmers have on Tomato farming in Alakasing Village, Peling Tengah District, Banggai Islands Regency is carried out in Alakasing Village, Peling Tengah District, Banggai Islands Regency, which starts from June-August 2022. The selection of the research site was carried out by purposive sampling based on the potential of adjusting to the purpose of the study. The analysis used in this study is income analysis. The results of the study obtained an analysis of the average income from the apple tomato farming business in Di Alakasing Village, Peling Tengah District, Banggai Islands Regency. during one growing season is IDR 10,981,381.95 in addition to that the feasibility of the R/C ratio of the Apple Tomato Farming Business is profitable with an average value of R/C = 4.05 That is, each additional input of IDR 1.00 will increase receipts of IDR 4.05. Suggestions that can be submitted after this research are: 1) The research data shows that the apple tomato farming business in Alakasing Village, Peling Tengah District, Banggai Kepulauan Regency, is profitable and effective, it also shows that this apple tomato farming business has good prospects to be developed by increasing the planting area. With the increase in acreage and good management, it will increase production and be followed by an increase in farmers' income. 2) It is recommended that there be management training for farmers. Whether it is training on technical farming or non-technical business such as training in analyzing farming business well. The results of this analysis can be used for the development of farming businesses, especially to obtain financing from capital-borrowing institutions